(untitled) (University of Warwick Press, 2022)
Each place is unique, not merely because of its size, number of houses, streams or waterways, but mainly because of its identity. This identity is formed by the relationships between people, the ways they live and how they express themselves within it. A space where local culture is expressed becomes a place. My place. A map can simply be the geographical representation of a space, but when it is created by those who truly know the area, it can also become a way of communicating, of telling a story, of strengthening one’s own identity. Through the project ’Accelerating the impact of citizen-generated data for improving the monitoring and management of catastrophic flooding’ a methdology of creating maps based on dialogue and with the participation of local residents was developed. This methodology was later applied in three Brazilian cities in the first half of 2022: • 06 de Agosto community in Rio Branco; • Guarani Kaiowá Occupation in Contagem, Minas Gerais; • Cai Cai community in São Paulo. These were extremely interesting experiences which endorsed that this can be a good way to achieve the goals defined by community members. The methodology has two main objectives: • The first is to promote participation through meetings between residents, researchers, public authorities and other stakeholders to generate maps that depict important issues in each area. • The second is to instigate and encourage discussions concentrated around the main themes identified in the produced maps. Maps can depict the challenges, difficulties, and needs of local residents, the activities they want to carry out and many other issues that would help and guide future improvement plans in the community. This manual briefly presents the methods and tools employed for mobilising residents and technical resources based on the mapping experiences in three different communities across Brazil. All activities undertaken followed the steps described in this manual. However, each community defined its issues in a distinct and particular way thus building its own tailored pathway for producing and discussing its maps. People have different backgrounds and the ways of applying the methodology need to allow adaptations, changes and new interpretations. The proposals presented in this manual are aimed at residents of urban neighbourhoods, marginalised communities, favelas, occupations and communities who wish to produce their maps, discuss important issues for their daily lives and collectively seek paths for a sustainable future. Shall we start? Uma versão em português está disponível